Illuminating causes and barriers underpinning forced labour in Nepal-Malaysia migration corridor - Andika Wahab; Abd Hamid Abd Murad; Romil Shamsuddin (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study problematises Malaysia's migrant workers' governance by highlighting that while it can address forced labour, it has no jurisdiction over the recruitment process in source countries. This study attempts to persuade that any efforts to eliminate forced labour should address root causes and barriers underpinning it through a comprehensive migration trajectory approach – i.e., pre-recruitment, pre-departure, and post-arrival (during employment) stages. This study focuses on the Nepal-Malaysia migration corridor as one of the essential labour migration pathways involving hundreds of thousands of Nepalis employed as temporary, unskilled, and low-wage labourers. Findings and subsequent analyses have been obtained through a workers' survey involving 76 Nepali workers in Malaysia, in-depth interviews with 28 Nepali workers and 13 Nepali community leaders in Malaysia, and five Nepali leaders in Nepal. Though this study specifically covers the Nepal-Malaysia migration corridor, the causes and systemic barriers discussed are highly relevant to other migration corridors (e.g., Indonesia-Malaysia and Bangladesh-Malaysia).